Somatodendritic consistency check for temporal feature segmentation - Toshitake Asabuki (Nature Portfolio, 2020)
The authors propose a learning rule for a neuron model with dendrite. In their model, somatodendritic interaction implements self-supervised learning applicable to a wide range of sequence learning tasks, including spike pattern detection, chunking temporal input and blind source separation.